A companion to World War I - Horne, John (Wiley-Blackwell, 2012)
A Companion to the First World War brings together an international team of distinguished historians who provide a series of original and thought-provoking essays on one of the most devastating events in modern history. Comprises 38 essays by leading scholars who analyze the current state of historical scholarship on the First World War. Provides extensive coverage spanning the pre-war period, the military conflict, social, economic, political, and cultural developments, and the wars legacy. Offers original perspectives on themes as diverse as strategy and tactics, war crimes, science and technology, and the arts.